Cleanliness and Health Of Pa.So.La Kitchen, The Ritz Carlton Jakarta Pacific Place - Auliya, Anisatul; Prianti, Diani; Fajrin, Annisa Nurul (JELAJAH: Journal of Tourism and Hospitality, 2024)
By implementing good hygiene and sanitation practices, employees can carry out their duties efficiently and produce high-quality food in Pa.So.La Kitchen, The Ritz-Carlton Pacific Place Hotel, which aligns with the hotel's motto, "We Are Ladies And Gentlemen Serving Ladies And Gentlemen". Data were collected through observation, interviews, and information from The Ritz-Carlton Pacific Place Hotel. This study shows that The Ritz-Carlton Jakarta Pacific Place Hotel's procedures have mostly met the company's standards regarding hygiene and sanitation. The benefits of this implementation include cleanliness of the kitchen area, adequate kitchen facilities, employee health, and the use of quality cleaning materials.